Racial and ethnic differences in survival in contemporary metastatic renal cell carcinoma patients, according to alternative treatment modalities - Luzzago, Stefano; Palumbo, Carlotta; Rosiello, Giuseppe; Knipper, Sophie; Pecoraro, Angela; Nazzani, Sebastiano; Tian, Zhe; Musi, Gennaro; Montanari, Emanuele; Shariat, Shahrokh F; Saad, Fred; Briganti, Alberto; et al. (Cancer causes & control, 2020)
PURPOSE: To test the association between African-American race and overall mortality (OM) rates in patients with metastatic renal cell carcinoma (mRCC). METHODS: Within the Surveillance, Epidemiology, and End Results registry (2006-2015), we identified patients with clear cell (ccmRCC) and non-clear cell mRCC (non-ccmRCC). African-Americans, Caucasians, and Hispanics were identified. Stratification was made according to histology and treatments: (1) no treatment, (2) systemic therapy (ST), (3) cytoreductive nephrectomy (CNT), (4) CNT + ST. Kaplan-Meier plots and multivariable Cox regression analyses were used. RESULTS: Of ccmRCC patients, 410 (7%), 4353 (75%), and 1005 (17%) were African-American, Caucasian, and Hispanic, respectively. Of non-ccmRCC patients, 183 (25%), 479 (65%), and 77 (10%) were African-American, Caucasian, and Hispanic, respectively. In ccmRCC, African-Americans were associated with higher OM rates (HR 1.20; 95% CI 1.05-1.37). Conversely, in non-ccmRCC, African-Americans were associated with lower OM rates (HR 0.75; 95% CI 0.59-0.97). CONCLUSION: African-American race is associated with prolonged survival in non-ccmRCC, but it is also associated with lower survival rates in ccmRCC. The exception to these observations consisted of patients treated with combination of CNT + ST for either ccmRCC or non-ccmRCC.
Keywords: karcinom z renálních buněk; Hispánci a Latinoameričané; mužské pohlaví; míra přežití; Male; senioři; Systemic therapy; Female; černoši nebo Afroameričané; Humans; ledviny; nádory ledvin; Caucasian; lidé; proporcionální rizikové modely; metastázy nádorů; Hispanic or Latino; Kidney; Cytoreductive nephrectomy; Kidney Neoplasms; ženské pohlaví; lidé středního věku; Middle Aged; African-American; Metastatic renal cell carcinoma; Black or African American; Proportional Hazards Models; Neoplasm Metastasis; běloši; Hispanic; Survival Rate; White People; Itálie; Aged; Carcinoma, Renal Cell; Italy